A reduction in marine primary productivity driven by rapid warming over the tropical Indian Ocean. Issue 2 (19th January 2016) - Roxy, Mathew Koll; Modi, Aditi; Murtugudde, Raghu; Valsala, Vinu; Panickal, Swapna; Prasanna Kumar, S.; Ravichandran, M.; Vichi, Marcello; Lévy, Marina
Abstract: Among the tropical oceans, the western Indian Ocean hosts one of the largest concentrations of marine phytoplankton blooms in summer. Interestingly, this is also the region with the largest warming trend in sea surface temperatures in the tropics during the past century—although the contribution of such a large warming to productivity changes has remained ambiguous. Earlier studies had described the western Indian Ocean as a region with the largest increase in phytoplankton during the recent decades. On the contrary, the current study points out an alarming decrease of up to 20% in phytoplankton in this region over the past six decades. We find that these trends in chlorophyll are driven by enhanced ocean stratification due to rapid warming in the Indian Ocean, which suppresses nutrient mixing from subsurface layers. Future climate projections suggest that the Indian Ocean will continue to warm, driving this productive region into an ecological desert. Key Points: Reduction of up to 20% in marine phytoplankton in the Indian Ocean during the past six decades Reduction in marine productivity is attributed to the rapid warming in the Indian Ocean Future climate projections indicate further warming and subsequent reduction in marine productivity